A Variable Threshold Image Secret Sharing Method. (May 2020) - Liu, Shanzheng; Zhang, Hang; Yu, Ying; Cai, Hongliang; Tang, Dan
Abstract: Image secret sharing has been widely discussed in recent years because of its high security. The threshold variable image secret sharing method is a hot research topic recently. The Lagrange interpolation method is easy to establish. Therefore, most of the existing secret sharing schemes are based on Lagrange interpolation polynomials. However, when the secret is updated, the existing secret sharing scheme needs to re-establish the polynomial, and the original computing resources cannot be utilized. When the cheater is found, it is not convenient to add or delete participants flexibly, resulting in a large waste of computer resources. Therefore, an image secret sharing method with variable threshold based on Newton interpolation method is proposed, which can reduce the computational complexity of the system and the amount of repeated computation. The experimental results show that the method is superior when the threshold is changed.